Alternative method for determining grain size distribution with use Doppler radar - Ortuta, Juraj; Greif, Vladimir; Brixová, Bibiana; Bednarik, Martin (Archives of Civil Engineering, 2026)
Blasting mining is a set of activities that can be divided into a sequence of repetitive tasks. Primarily it is drilling, blasting, loading with the hauling and crushing. Drilling and blasting have the greatest impact on the economic indicator of the whole process. Their aim is to achieve the most optimal fragmentation of the blasting wall. It follows that an accurate and efficient fragmentation assessment process is one of the main indicators of blasting efficiency. Nowadays, sieve analysis is the most accurate method. However, this is a time-consuming and labour-intensive method. This is a predictive method, the disadvantage of which is the absence of the actual fragment size, which is also associated with inaccuracy. Currently, when the emphasis is on optimizing processes with environmental impact, finding a more efficient evaluation method that provides more accurate results than classical prediction procedures is even more relevant. The question of evaluating the grain size has been considered by many experts. This paper discusses the use of the reflection of flying fragments and their evaluation by Doppler radar directly during blasting. These measurements specify the size of the fragments and blasting speed up the process of evaluating the grain size of the muck-pile material.